'Music for the Wretched': Euripides' Trojan women as refugee theatre. (14th April 2019) - Eberwine, Paul
Abstract: In the dramatic production Syria: The Trojan Women (2013 ) and its successor Queens of Syria (2016 ), casts of female Syrian refugees adapt Euripides' Trojan Women to frame and comment on their experiences of war. This article considers these productions' modes of adaptive fidelity to their ancient source. Syria: The Trojan Women transhistorically analogizes the Trojan Women to the experiences of contemporary Syrian women, using it as a tool to build comprehensible narratives around the performers' trauma. Queens of Syria builds on its predecessor by critiquing the use of Greek tragedy as an adaptive frame, challenging the audience to account for tragedy's role in structuring their expectations of what counts as 'authentic' grief. This self-critical aspect recalls metapoetic elements of the Trojan Women itself. In this sense, Queens of Syria echoes its source text even while critically interrogating it, offering a historically conscious framework for adaptation through critique.